Chromosome aberrations in chloralkali workers previously exposed to mercury vapor. - Hansteen, Inger Lise; Ellingsen, Dag G.; Clausen, K. O.; Kjuus, Helge (Scandinavian Journal of Work, Environment & Health, 1993)
Chromosome aberrations and micronuclei in peripheral lymphocytes were studied in 29 male chloralkali workers previously exposed to mercury vapor and in two matched reference groups comprising 29 nitrate fertilizer workers and 29 customs and police officers. The study was performed using whole-blood cultures with and without hydroxyurea and caffeine to inhibit deoxyribonucleic acid synthesis and repair, respectively. No significant differences in the frequencies of chromosome aberrations and micronuclei were observed. However, a nonsignificant increase in chromosome breaks and dicentrics was found in the subgroups with high urinary mercury peak levels or high cumulative mercury exposure. An increased prevalence of "high" scores of chromatid breaks in the inhibited cultures, exceeding the 75th percentile of all of the subjects studied, was observed for the chloralkali workers when compared with both reference groups. No evident cytogenetic effects were observed among the chloralkali workers with the methods used in the present study.